بەرنامەی گفتوگۆی تەلەڤزیۆنیی لەگەڵ رەنج و رەنگدانەوەی ئاسایشی کۆمەڵایەتی توێژینەوەیەکی ناوەرۆکشیکارییە - مجید, پ.د.هێمن; حسن, پ.ی. بەناز حمەڕشید (Sulaimani Journal for Humanities, 2023)
This research, which entitled "Le Gell Renj television conversation program and the reflection of social security", is a content analysis study, aims to identify social security and its foundations such as political stability, social unity, economic and economic unity. Life, according to the selection of the hands, knowing the proportion of the gender and profession of guests and the type of audience and women, as well as what the topics of the program are said in the program, knowing the purpose, discourse of the program, the positive and negative aspects of the program, and how it was said, the way of this The research is an analysis description of the use of analysis form tools by creating groups and units. The discussion of this research is taking the duration of (3) months of the program with effort, which is (11) programs that are broadcast weekly, in the results of this And research, in the highest proportion of guests according to male race and the highest rate of government postal profession, in most subjects the economy and living and service is the most and including local products are the most subjects, among the social subjects The issue of drugs is the most, and in the most directions, the negative direction is the highest rate, which has a negative effect on the recipient.
Keywords: بەرنامەی تەلەڤزیۆنی ئاسایشی کۆمەڵایەتی